Questioning Sexual Diversity in Andre Aciman’s Call Me by Your Name and Brent Hartinger’s Geography Club - Pramesti, Tri; Litaay, Adeline Grace Mariana (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
This paper discusses sexual diversity exposed in Andre Aciman’s Call Me by Your Name and Brent Hartinger’s Geography Club. Both novels tell stories about sexual orientation and its impact on the daily lives of the main characters, who are high school students. In Call Me by Your Name, Aciman depicted Elio as a teenager who admires people of the same sex, and in Geography Club, Russell Middle Brook disguises his sexual orientation because he is gay. Using Sociology of Literature as an approach, more specifically queer theory as a means of carrying out queer criticism, this research aims to discuss sexual diversity exposed in these two fictions. It also talks about the heteronormative pressures experienced by the two figures above during their high school years as students who had different sexual orientations. The research results show that although schools and society always emphasize diversity, sexual diversity is not yet accepted. The heteronormative pressure that the experience of Elio and Russel comes from their close environments, such as parents, friends, and school. Elio and Russel need to keep their true sexual identities because showing sexual diversity for high school students is taboo. They also have to keep their sexual orientation to safeguard their lives from rejection and bullying. Selecting the two novels as the data sources helps to understand each text individually and acknowledge how different authors approach similar themes.